Epigenetic modifications in plant abiotic stress adaptation: towards climate-resilient and sustainable crop improvement - Qadir, Muslim; Kaur, Navjot; Rahman, Faiz Ur; Nabi, Farhan; Ahmed, Zienab F. R.; Wu, Jian (Frontiers in Plant Science, 2026)
Abiotic stresses such as drought, salinity, heat, and cold are the most critical factors limiting global crop productivity, posing significant challenges to food security and the sustainability of agricultural systems. Epigenetic modifications, including DNA methylation, histone modifications and non-coding RNAs, enable plants to respond rapidly to environmental stimuli without altering DNA sequences. These mechanisms, demonstrated through studies using whole-genome bisulfite sequencing (WGBS), ChIP-seq, ATAC-seq, and validation in key mutants (met1, hda6, brahma), mediate chromatin remodelers (SWI/SNF, DDM1), hormone signaling crosstalk, and emerging spatial epigenomics (scATAC-seq in roots and guard cells). This review synthesizes the hierarchy of somatic stress memory, characterized by sustained H3K4me3 enrichment at promoters that facilitates rapid re-induction and transgenerational inheritance mediated by RdDM across the F1-F3 generations. By distinguishing correlative profiling from causal evidence, this review bridges significant experimental gaps, highlights the intricate, dynamic interplay between epigenetic layers that underpins stress memory and its heritable effects. Crop applications reveal the role of natural epialleles in promoting resilience: hypomethylation of OsHMA3 promoter confers cadmium tolerance in rice grains (>50% reduction), while DRO1 demethylation enhances drought adaptation over deeper rooting (15-22% yield protection). CRISPR-dCas9 epigenome editing enables targeted modifications, with OsDREB1 targeting in rice boosting drought tolerance by 25% and TaNHX1 modification in wheat developing salinity resilience. These advances position epigenetic regulation as a transformative tool for climate-resilient crop breeding. Integrating multi-omics with functional genomics addresses polyploid challenges, enabling non-transgenic epiallele breeding for global food security.